2020
DOI: 10.1021/jacs.0c01073
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Origin of One- or Two-Step Valence Tautomeric Transitions in Bis(dioxolene)-Bridged Dinuclear Cobalt Complexes

Abstract: Valence tautomerism (VT) involves a reversible stimulated intramolecular electron transfer between a redox-active ligand and redox-active metal. Bis(dioxolene)-bridged dinuclear cobalt compounds provide an avenue toward controlled two-step VT interconversions of the form {Co III -cat-cat-Co III } ⇌ {Co III -cat-SQ-Co II }⇌{Co II -SQ-SQ-Co II } (cat 2− = catecholate, SQ •− = semiquinonate). Design flexibility for dinuclear VT complexes confers an advantage over two-step spin crossover complexes for future appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
122
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(135 citation statements)
references
References 73 publications
13
122
0
Order By: Relevance
“…The direct dependence of the character (one‐ or two‐step) and the degree of completion of VT transition on the redox‐potential of the ligand was recently shown on the example of a series of complexes with brominated spiro‐conjugated bis(dioxolene) ( Br 4 spiroH 4 ) (Scheme 16). [61] Bromine derivative [Co 2 ( Me 3 TPA ) 2 ( Br 4 spiro )] 2+ is capable to undergo a partial VT interconversion { HS Co II −(SQ−Cat)− LS Co III }→{ HS Co II −(SQ−SQ)− HS Co II }, while its unsubstituted analog [Co 2 ( Me 3 TPA ) 2 ( spiro )] 2+[60] is in the high‐spin state over a wide temperature range. Experimental and theoretical research has shown the possibility to control VT behaviour of dinuclear cobalt complexes by means of modification of the redox‐active and ancillary ligands.…”
Section: Quinonoid‐bridged 3 D‐metal Complexes With Tetradentate N‐donor Basesmentioning
confidence: 99%
“…The direct dependence of the character (one‐ or two‐step) and the degree of completion of VT transition on the redox‐potential of the ligand was recently shown on the example of a series of complexes with brominated spiro‐conjugated bis(dioxolene) ( Br 4 spiroH 4 ) (Scheme 16). [61] Bromine derivative [Co 2 ( Me 3 TPA ) 2 ( Br 4 spiro )] 2+ is capable to undergo a partial VT interconversion { HS Co II −(SQ−Cat)− LS Co III }→{ HS Co II −(SQ−SQ)− HS Co II }, while its unsubstituted analog [Co 2 ( Me 3 TPA ) 2 ( spiro )] 2+[60] is in the high‐spin state over a wide temperature range. Experimental and theoretical research has shown the possibility to control VT behaviour of dinuclear cobalt complexes by means of modification of the redox‐active and ancillary ligands.…”
Section: Quinonoid‐bridged 3 D‐metal Complexes With Tetradentate N‐donor Basesmentioning
confidence: 99%
“…Such thermal stability of valence tautomers indeed facilitated their structural/spectroscopic authentication even at ambient conditions. Though interconversion was not observed up to a temperature of 373 K, heating of 2 a in 1‐butanol at ≈393 K for 12 h yielded minor quantity of 2 b , suggested the two energy minima were separated by a very substantial energy barrier [4d] …”
Section: Figurementioning
confidence: 97%
“…Valence tautomeric (VT) complexes derived from redox‐active ligands and metal centers, represented by metal‐dioxolene complexes, can take two valence isomers or redox isomers with different localized electronic structures exhibiting different physical properties [8] . VT transitions between these isomers accompanying intramolecular electron transfer can not only cause changes in the valence and spin states and radical formation and disappearance but also lead to interesting mixed‐valence states [9] and spin transitions, [2a–c, 10] and these features can be tuned by controlling the VT transitions by external stimuli, such as heat, [10a, f, g, 11] light, [1g, 10e, f, 12] X‐ray, [13] pressure, [3g] and electric [14] and magnetic fields [15] . Therefore, VT transitions are widely utilized as stimuli‐responsive, controllable functions on dynamic molecular crystals.…”
Section: Introductionmentioning
confidence: 99%